Effects of obesity on hormonally driven cancer in women - Moley, Kelle H. (Sci Transl Med, 2016)
Obesity increases the risk of numerous poor health outcomes, including cancer. Obesity is especially problematic in women because both they and their offspring may be at increased risk of cancer. Studying transmission of obesity-induced cancer risk is challenging in humans, but animal studies are beginning to reveal the underlying mechanisms.